A dictionary of economics - Black, John 1931-; Hashimzade, Nigar 1964-; Myles, Gareth D. 1961- (Oxford Univ. Press, 2009)
Includes 2,500 key economic terms with clear, concise definitions. It covers all aspects of economics including economic theory, applied microeconomics and macroeconomics, labor economics, public economics and public finance, monetary economics, environmental economics, and many others. There is strong coverage of international trade and many entries on economic organizations and institutions from around the world. This edition contains expanded coverage of common econometric concepts and highlights major theoretical concepts including agency, competition, equilibrium. Fully revised and updated, this edition now features recommended web links at entry level.
Keywords: Wirtschaft; Economics -- Dictionaries; Wirtschaftswissenschaften; Englisch; Volkswirtschaftslehre; Volkswirtschaft; Wörterbuch